CHARACTERIZATION OF PHARMACOKINETICS OF 2-((3-(CHLOROMETHYL)BENZOYL)OXY) BENZOIC ACID IN RATS BY USING HPLC-DAD METHOD - Caroline; Sie, Nathania; Foe, Kuncoro; Esar, Senny Yesery; Jessica, Maria Anabella (International Journal of Applied Pharmaceutics, 2019)
Objective: A new compound of salicylic acid derivative, namely 2-((3-(chloromethyl)benzoyl)oxy)benzoic acid (3CBB), was synthesized to find a compound exhibiting higher analgesic activity and smaller ulcer irritation than acetylsalicylic acid (ASA). Therefore, this study aimed to investigate the pharmacokinetics of this new compound in rats, following a single dose oral administration of 3CBB (45 mg/kg BW). Methods: Plasma samples of 9 healthy rats were collected before and up to 3 h after its oral administration, following an 18 h fasting period. Plasma concentrations of 3CBB were determined using a validated HPLC-DAD assay. Pharmacokinetic parameters were determined using the compartment model technique. All experiments were carried out in triplicate. Results: The pharmacokinetic parameters of 3CBB obtained were as follows: Tmax= 28.9±1.1 min, Cmax = 0.57±0.02 µg/ml, AUCtotal = 66.3±1.0 µg min/ml, Kel = 0.018±0.002 min-1, and T1/2el = 39.4±3.9 min. The long elimination half-life and low Cmax indicated that 3CBB was extensively distributed in the deep and very deep tissues. This confirmed the unique and special characteristics of a highly lipophilic compound like 3CBB (log P = 3.73). Conclusion: 3CBB demonstrated a slower onset of action and longer elimination time from the body compared to ASA. Thus this new compound is a potential candidate to be developed as a new drug.